FAO animal production and health paper N119: Manual on meat inspection for developing countries - D Herenda (FAO, 1994)
This book has been prepared by an experienced meat inspection specialist at the main author in cooperation with meat inspection experts from the four regions Asia and Pacific, Africa, Latin America and the Near East. The book is intended to guide meat inspectors particularly in the four mentioned in their daily work in urban and rural abattoirs.